Optimization Design of Part Tolerance of RV Reducer based on Genetic Algorithm - Xie Xiongwei; Xu Honghai; Guan Tong (Jixie chuandong)
The backlash is one of the important technical indicators of the RV reducer， and there are many design parameters that affect the backlash. Based on the mathematical model between the part processing feature tolerance and cost， the minimum part processing cost is taken as the target， the allowable backlash(≤1′) and the assembly dimension chain are used as the constraints， and the genetic algorithm is used to optimize the key dimensional tolerances of the RV reducer cycloidal gear， pinwheel， crankshaft and other parts. The CATIA software is used to establish the 3D virtual prototype of the RV reducer considering the limit error of the part size， and the virtual prototype is imported into the Adams software for the simulation of the backlash. The simulation results show that the backlash of the RV reducer is 0.002′~1.07′， which is close to the allowable backlash (≤1′). The correctness of the proposed part tolerance optimization design method is verified， which has important reference value for improving the transmission precision of RV reducer and controlling the processing cost of parts.